Theories of psychotherapy in addiction - Yıldız, Muhammed; Tamam, Lut (Journal of Dependence, 2025)
Addiction, both substance addiction and behavioral addictions, is a phenomenon that affects individuals at increasing rates and at early ages, with devastating health, psychological and social effects. Fighting addictions, like other prevention activities, consists of primary, secondary and tertiary prevention activities. While the main thing in primary prevention studies is that the individual never encounters addiction, the aim of secondary prevention studies is to support the individual in the process of getting rid of addiction. One of the most important of these supports is psychotherapy studies carried out with addicted individuals. Psychotherapy involves the individual’s ability to cope with his/her psychological problems, increase his/her psychological resilience against difficulties, improve his/her skills in coping with his/her problems, and become spiritually stronger in a holistic sense. In psychotherapies in the fight against addiction, therapeutic studies are carried out on the individual’s ability to cope with substance use or behavioral addiction. In the studies to be carried out by mental health experts working in the field of addiction, knowing psychotherapy theories well and acquiring addiction-specific methods of these theories will help the psychotherapy processes to be successful. In this study, psychotherapy theories that are widely used today and have specific methods in combating addictions are examined. Psychotherapy theories are examined in four sections. The basic features of each theory, how it explains addiction, what it aims at in the psychotherapy process, and empirical studies in the literature are included. In this article, it is aimed for mental health professionals working in the field to combat addictions to gain a perspective on the case formulations they will use in psychotherapy studies.